2022
DOI: 10.1186/s12870-021-03421-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and regulation mechanism analysis of ubiquitin-conjugating family genes in strawberry reveals a potential role in fruit ripening

Abstract: Background E2 ubiquitin-conjugating (UBC) enzymes are an integral component of the ubiquitin proteasome system that play an important role in plant development, growth, and external stress responses. Several UBC genes have been identified in various plants. However, no studies exploring the functions of UBC genes in regulating fruit of strawberry have been reported. In the present study, a systematic analysis of the entire UBC family members were conducted in the genome of strawberry (Fragaria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…Gene duplication events such as tandem duplication, WGD, and segmental duplication occurring during genome evolution are the main sources that give rise to gene expansion, and they have remarkable roles in plant growth, development, and adaptability to various stresses. Our result showed that the expansion of FaERFs was mainly due to WGD/segmental duplication, which was consistent with our previous studies in MAPK [37], UBC [38], GMP [39], and GST [40] gene families of the cultivated strawberry. In addition, we found that the number of FaERFs in the B-3 group was significantly greater than other groups by gene duplication, implying that B-3 of FaERFs had significant expansion through the evolution of cultivated strawberries.…”
Section: Discussionsupporting
confidence: 93%
“…Gene duplication events such as tandem duplication, WGD, and segmental duplication occurring during genome evolution are the main sources that give rise to gene expansion, and they have remarkable roles in plant growth, development, and adaptability to various stresses. Our result showed that the expansion of FaERFs was mainly due to WGD/segmental duplication, which was consistent with our previous studies in MAPK [37], UBC [38], GMP [39], and GST [40] gene families of the cultivated strawberry. In addition, we found that the number of FaERFs in the B-3 group was significantly greater than other groups by gene duplication, implying that B-3 of FaERFs had significant expansion through the evolution of cultivated strawberries.…”
Section: Discussionsupporting
confidence: 93%
“…Two UBC enzymes are connected with ripening in strawberry fruit. One has a positive effect on fruit development, ripening, and softening by upregulating anthocyanin accumulation and significantly increasing expression of maturity-related genes, whereas the other increases fruit firmness [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the expression levels of some ripening-related genes were significantly increased or decreased. Based on previous reports (Yu et al, 2020;Li et al, 2022), we speculated that FaU-box127 may regulate fruit ripening by affecting the ABA or sucrose pathways, but the mechanism is still unclear and it needs further study.…”
Section: Discussionmentioning
confidence: 92%
“…Studies on strawberry fruit development and ripening have focused on the regulatory roles of ABA ( Li et al., 2011 ), auxin ( Mezzetti et al., 2004 ), and sucrose ( Luo et al., 2020 ). Furthermore, we have previously found the E2 ubiquitin-conjugating enzyme genes play a vital role in strawberry ripening ( Li et al., 2022 ), whereas, whether and which U-box E3 ubiquitin ligase gene members in strawberry are related to stress responses and fruit ripening is still unknown. In this study, we carried out genome-wide characterization analysis of U-box genes in cultivated strawberry by concentrating on the gene location, gene structure, evolutionary analysis, functional and protein-protein interaction analysis.…”
Section: Introductionmentioning
confidence: 99%